KAJIAN FILOSOFIS PRO DAN KONTRA DILARANGNYA EUTHANANSIA - Isnawan, Fuadi (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2016)
Life is derived by all humankind of any race or class without exception. These rights is the fundamental right of every human being in this world. Even in the medical world of medicine, there is a very famous oath, the oath Hiprokrates which states that any doctor would keep the lives of every human being, from birth to death the man. Here the medical profession spearhead the implementation of the oath, and every doctor should perform their duties based on the oath they say before they undergo the profession. Each physician is required to maintain the lives of patients - patients, should megupayakan various things in order to examine the patient lives of these patients can be saved. It can be concluded that every doctor should keep every person's life and can not be the God to end the life of his patient, whether intentionally or not, or the so-called euthanasia, the doctor puts a series of measures to end the lives of patients who are already in the terminal stages.